Antecedents dan Outcomes Orientasi Pemasaran Digital: Tinjauan Systematic Literature Review - Andhi Febisatria (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the role of Digital Marketing Orientation as a strategic foundation for enhancing marketing performance and business performance in the era of digital transformation. A Systematic Literature Review approach is employed to synthesize empirical and conceptual findings from relevant scholarly literature. Results indicate that Digital Marketing Orientation is shaped by digital marketing capabilities, customer orientation, analytical capability, organizational readiness, and strategic leadership. Variations in the impact of digital marketing orientation on organizational outcomes are influenced by differences in industry context, levels of digital maturity, and methodological approaches. Findings highlight the contextual nature of Digital Marketing Orientation and underscore the importance of mapping mediation and moderation mechanisms in digital value creation.